The relationship between students’ types of intelligence according to Gardner and their academic achievements in the general physics course - Igenbayeva, A.S.; Nurgaliyeva, K.E.; Karstina, S.G.; Shageeva, F.T. (Recent Contributions to Physics, 2026)
The article examines the influence of different types of students’ intelligence, classified according to Howard Gardner’s theory of multiple intelligences, on their academic performance in general physics. The study involved 58 first grade bachelor students enrolled in the educational program Intelligent Control Systems. According to their dominant type of intelligence, the students were divided into three subgroups: Hard Skills, Soft Skills, and Hard/Soft Skills. The classification was based on the dominant abilities formed as a result of the prevalence of particular types of intelligence identified by Gardner. Based on the results of tests in mechanics and electromagnetism, the academic performance of each group was evaluated. The analysis showed that students with dominant Hard Skills intelligence (logical–mathematical, naturalistic, and kinesthetic) demonstrated the highest results (average score of 93.3%), whereas students with Soft Skills intelligence (intrapersonal, interpersonal, and existential) and mixed types (linguistic, musical, and visual–spatial) showed comparatively lower academic performance. The findings highlight the importance of considering students’ cognitive profiles when organizing the educational process and developing differentiated teaching methods. The results may be useful for teachers of natural sciences and specialists in the field of pedagogy.